2005
DOI: 10.1021/bi050650l
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Amyloid β Peptide Degrading Enzymes to Oxidative Damage:  A Potential Alzheimer's Disease Spiral

Abstract: Insulysin (IDE) and neprilysin (NEP) were found to be inactivated by oxidation with hydrogen peroxide, an iron-ascorbate oxidation system, and by treatment with 2,2'-azobis(2-amidinopropane) dihydrochloride (AAPH). In each case reaction led to the introduction of protein carbonyl groups as judged by reaction with 2,4-dintrophenylhydrazine. IDE was inactivated by reaction with 4-hydroxy-2-nonenal (HNE) with the concomitant formation of protein adducts. NEP was not inactivated to a significant extent by HNE, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
78
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(84 citation statements)
references
References 30 publications
(51 reference statements)
4
78
0
Order By: Relevance
“…IDE is a metalloprotease responsible for degradation of both insulin and Aβ, and reduced IDE levels in sAD leading to decreased Aβ degradation significantly contribute to the disease pathophysiology. Literature data indicate that iron-induced oxidative stress inactivates IDE (Shinall et al 2005) which might provide an explanation why iron-chelators like M30 could have beneficial effect at the level of IDE, as detected in our experiments for the first time. Decreased IDE protein and gene expression has been found in STZ-icv rat model also by others (Yang et al 2014), but our recent 9-month follow up data on staging of cognitive, neuropathological and neurochemical changes in STZ-icv rat model has shown that the order of pathology appearance after STZ-icv treatment is: tau protein/2 weeks, IDE/1 month, and amyloid β/3 months (Osmanovic Knezovic et al 2015), which supports the results presented here.…”
supporting
confidence: 74%
“…IDE is a metalloprotease responsible for degradation of both insulin and Aβ, and reduced IDE levels in sAD leading to decreased Aβ degradation significantly contribute to the disease pathophysiology. Literature data indicate that iron-induced oxidative stress inactivates IDE (Shinall et al 2005) which might provide an explanation why iron-chelators like M30 could have beneficial effect at the level of IDE, as detected in our experiments for the first time. Decreased IDE protein and gene expression has been found in STZ-icv rat model also by others (Yang et al 2014), but our recent 9-month follow up data on staging of cognitive, neuropathological and neurochemical changes in STZ-icv rat model has shown that the order of pathology appearance after STZ-icv treatment is: tau protein/2 weeks, IDE/1 month, and amyloid β/3 months (Osmanovic Knezovic et al 2015), which supports the results presented here.…”
supporting
confidence: 74%
“…61,62 The transcription factor, hypoxia-inducible factor 1, is increased during hypoxia and could also play a key role in the hypoxia-induced decrease in NEP expression we have observed. 63 Alterations in NEP degradation may be important, although this is an understudied area.…”
Section: Discussionmentioning
confidence: 81%
“…Oxidative stress manifested by lipid and protein oxidation among other indices is observed in most of the neurodegenerative and neurotoxic disorders, both as a cause and a consequence of the pathogenic pathways. In AD, ROS, the primary mediators of oxidative stress, seem to be either directly or indirectly involved in the production of amyloid b-peptides, 27 a keystone in AD. Simultaneously, ROS generated FIGURE 3 PCA of second derivative infrared spectra in the 900-800 cm 21 region from brain tissues (control (l) and amphetamine treated (~) animal).…”
Section: Changes In Lipid Peroxidation and Protein B-sheet Content Inmentioning
confidence: 99%